Macrophages as homeostatic regulators in the ischemically damaged myocardium after use of allogenic biomaterial - A. I. Lebedeva; S. A. Muslimov; E. M. Gareev; S. A. Afanasiev; D. S. Condratyeva; S. V. Popov (Бюллетень сибирской медицины, 2020)
Macrophages as the effector cells play a key role in initiating the inflammatory process and predetermine the manifestation of the postinfarction cardiosclerosis. The population of these cells is heterogenous and is mainly represented by M1 and M2 phenotypes. Alloplant biomaterial (ABM) is resorbed by the macrophages which became the regulators of the cellular interaction in tissues.The aim of the investigation was to reveal the peculiarities of the postinfarction healing of the myocardium following the ABM insertion and to assess the population change in the dynamics of macrophages and c-kit+ cells.Materials and methods. The experimental investigations were carried out on 100 male Wistar’s rats weighing 0.18–0.25 kg. All the animals had coronary occlusion by way of ligating the arteries. In the experimental group, the ABM (12 mg) suspension was intramyocardially administered simultaneously with the vessel stricture formation. The harvesting of hearts was carried out at 3, 7, 14, 30, 45 days.Results. In the experimental group the course of the inflammatory process was characterized by the onset of the early proliferative stage, whereas in the control group colliquative necrosis was developing. It was caused by different degrees of the macrophage reaction expression. The number of CD68+ cells in the rat reactive zone of the control group was bigger than in the experimental one. In the experimental group the ABM-induced macrophages of mesenchyme origin were revealed and с-kit+ cells were considerably more in number than in the control one. After 45 days, the scar area index in the experimental group was significantly less than in the control group.Conclusion. ABM had a histoprotective effect under the conditions of the acute myocardial ischemia due to the inhibition of macrophage migration and induction of cellular cardiomyogenesis.